Synthesis of polybenzoxazine/clay nanocomposites by in situ thermal ring‐opening polymerization using intercalated monomer - Demir, K. D.; Tasdelen, M. A.; Uyar, T.; Kawaguchi, A. W.; Sudo, A.; Endo, T.; Yagci, Y. (Wiley, 2011)
AbstractA new class of polybenzoxazine/montmorillonite (PBz/MMT) nanocomposites has been prepared by the in situ polymerization of the typical fluid benzoxazine monomer, 3‐pentyl‐5‐ol‐3,4‐dihydro‐1,3‐benzoxazine, with intercalated benzoxazine MMT clay. A pyridine‐substituted benzoxazine was first synthesized and quaternized by 11‐bromo‐1‐undecanol and then used for ion exchange reaction with sodium ions in MMT to obtain intercalated benzoxazine clay. Finally, this organomodified clay was dispersed in the fluid benzoxazine monomers at different loading degrees to conduct the in situ thermal ring‐opening polymerization. Polymerization through the interlayer galleries of the clay led to the PBz/MMT nanocomposite formation. The morphologies of the nanocomposites were investigated by both X‐ray diffraction and transmission electron microscopic techniques, which suggested the partially exfoliated/intercalated structures in the PBz matrix. Results of thermogravimetric analysis confirmed that the thermal stability and char yield of PBz nanocomposites increased with the increase of clay content. © 2011 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2011
Keywords: Benzoxazine; Polymers; X ray diffraction; high performance polymers; Ring opening polymerization; Ion exchange reactions; Nanocomposites; Sodium ions; nanocomposites; Organomodified clay; Metal ions; Benzoxazine resin; thermosets; benzoxazine resins; Char yield; in situ polymerization; Monomers; Nanocomposite formations; In-situ; Intercalated monomers; X ray diffraction analysis; clay; Polybenzoxazine; Thermogravimetric analysis; Thermosets; matrix; Benzoxazine monomers; polybenzoxazines; Synthesis (chemical); Clay content; Microscopic techniques; Transmission electron; High performance polymer; Ion exchange